Establishment of reference interval for thyroid-stimulating hormone using electrochemiluminescence assay in a healthy adult population from Fortaleza, Brazil - Gurgel,Maria Helane C (2020)
ABSTRACT Objective This study aimed to determine the thyroid-stimulating hormone (TSH) reference interval (RI) and to assess the influence of the use of thyroid ultrasonography (TUS) on reference individual selection from a healthy adult population in Fortaleza, Brazil. Subjects and methods This cross-sectional study recruited patients (N = 272; age = 18-50 years) with normal thyroid function (NTF) and placed them in three groups according to their test results: NTF (n = 272; all participants), TUS (n = 170; participants who underwent thyroid US), RI (n = 124; reference individuals with normal TSH levels). TSH, FT4, TT3, TgAb, and TPOAb concentrations were determined by electrochemiluminescence assay. TUS was performed using a 7-12 MHz multifrequency linear transducer by two radiologists. The 2.5th and 97.5th percentiles of the distribution curve corresponded to lower and upper TSH RI levels, respectively. Results The mean TSH level was 1.74 ± 0.96 mIU/L, and TSH range was 0.56-4.45 mIU/L. There was no difference in the TSH concentrations between men and women nor between the groups. TUS did not appear to be an essential tool for the reference group selection. Conclusion The upper limit of TSH was comparable to the reference interval provided by the assay manufacturer (4.45 vs. 4.20 mIU/L) but the lower limit was not (0.56 vs. 0.27 mIU/L). This finding may have a clinical impact since these values may lead to the misdiagnosis of euthyroid patients with subclinical hyperthyroidism.